Impact of enhancing national autonomous innovation demonstration zones on cities’ efficiency in technological innovation - Mei He; Zhixiong Fan; Yanrui Chen (Scientific Reports)
Abstract National independent innovation demonstration zones (NIIDZs) play a crucial role in scientific and technological innovation (STI). However, there have long been disputes regarding their ability to continuously increase urban STI efficiency, the paths through which they generate innovation-driven effects, and their spatial effects. This study uses the panel data of 274 cities in China from 2006 to 2020 and applies various methods including the multiperiod difference-in-differences model, quantile model, and spatial Durbin model to systematically explore the impact of NIIDZs on urban STI efficiency. The research findings are as follows: the positive impact of NIIDZs on urban STI efficiency begins to emerge in the fourth year after their establishment and persists. The spatial effect is distance dependent, suppressing the STI efficiency of surrounding cities within 110 kms while promoting that of areas at a distance between 110 and 410 kms, with the strongest effect occurring at 360 kms. The mechanism analysis shows that NIIDZs affect urban STI efficiency through factor agglomeration, innovation environment optimization, and industrial structure transformation and upgrading. This study provides important policy insights for fully harnessing the innovation-driven effect of NIIDZs to increase urban STI efficiency.